How well does Anorexia Nervosa fit with personal values? An exploratory study. Issue 1 (December 2016) - Mulkerrin, Úna; Bamford, Bryony; Serpell, Lucy
Abstract Background Despite an increasing clinical interest in the use of personal values as a motivational tool in psychological therapies for Anorexia Nervosa (AN), research is limited. This study explored personal values among individuals with AN, with a particular focus on the 'fit' between participants' values and their AN. Methods A qualitative research design was employed in this study. In-depth, semi-structured interviews were carried out among eight female outpatients and inpatients with a diagnosis of AN or Eating Disorder Not Otherwise Specified – AN type (EDNOS-AN type). Data was analysed using Interpretative Phenomenological Analysis (IPA; Smith, Jarman & Osborne, 1999). Results Three super-ordinate themes emerged from analysis: 'Balancing Values' (difficulty finding balance in relating to and acting on values), 'Congruence and Clashes between AN and Values' (experiences of AN representing a mixed-fit with values) and'From Ambivalence to Motivation' (ambivalence toward both AN and recovery – in the context of its mixed-fit with values – and experiences of values as a motivational tool in recovery). Conclusions Study findings support a role for psychological therapies in working with personal values as a means of promoting recovery in AN, through supporting individuals to explore AN's workability in the context of their values. Further research investigating the optimal stage of treatment to work with values as a motivational tool is warranted.